Nonlinear optical properties of metal free thio alkyl and tert-butyl phenoxy phthalocyanine - Joseph, Otto (Rhodes University, Faculty of Science, Department of Chemistry)
This work reports on the nonlinear optical properties of tetra - and octa substituted phthalocyanines (Pcs) utilising pentane thiol and 4-tertbutyl phenol as substituents. Their nonlinear absorption coefficient (ð ›½) and absorption cross sections were determined using the Z-scan technique with a 10 ns pulse laser at 532 nm. The molecular second order hyperpolarizability Im[Î³] was observed and the following Im[Î³] trend was obtained for ð ›¼-H2Pc(SC5H11)4 isomers, 5.93 Ã—10âˆ’31 (Cs) 2.24Ã—10âˆ’32(D2h) > 1.21Ã—10âˆ’32(C4h) > 1.05Ã—10âˆ’32 (C2v) esu, respectively, in chloroform. Symmetry was seen to have an effect on the observed reverse saturable absorption (RSA) response. Based on the five level model rate equation nonlinear fit of the RSA response curves and Real Time Time Dependant Density Functional Theory (RT-TDDFT) results, the singlet excited state population dynamics was found to play a significant role in producing the observed Im[Î³] trend.
Keywords: Nonlinear optics; Phthalocyanines; Time-dependent density functional theory; Magnetic circular dichroism; Reverse saturable absorption (RSA); Real Time Dependent Density Functional Theory (RT-TDDFT)